Brain-machine interface-based training for improving upper extremity function after stroke: A meta-analysis of randomized controlled trials - Xie, Yu-lei; Yang, Yu-xuan; Jiang, Hong; Duan, Xing-Yu; Gu, Li-jing; Qing, Wu; Zhang, Bo; Wang, Yin-xu (Frontiers in Neuroscience, 2022)
Background: Upper extremity dysfunction after stroke is an urgent clinical problem that greatly affects patients' daily life and reduces their quality of life. As an emerging rehabilitation method, brain-machine interface (BMI)-based training can extract brain signals and provide feedback to form a closed-loop rehabilitation, which is currently being studied for functional restoration after stroke. However, there is no reliable medical evidence to support the effect of BMI-based training on upper extremity function after stroke. This review aimed to evaluate the efficacy and safety of BMI-based training for improving upper extremity function after stroke, as well as potential differences in efficacy of different external devices. Methods: English-language literature published before April 1, 2022, was searched in five electronic databases using search terms including "brain-computer/machine interface", "stroke" and "upper extremity." The identified articles were screened, data were extracted, and the methodological quality of the included trials was assessed. Meta-analysis was performed using RevMan 5.4.1 software. Results: A total of 17 studies with 410 post-stroke patients were included. Meta-analysis showed that BMI-based training significantly improved upper extremity motor function [SMD=0.62; 95% CI (0.34,0.90); I2 = 38%; p <0.0001; n=385; moderate-quality evidence]. Subgroup meta-analysis indicated that BMI-based training significantly improves upper extremity motor function in both chronic [SMD=0.68; 95% CI (0.32,1.03), I2 = 46%; p = 0.0002, random-effects model] and subacute [SMD=1.11; 95%CI (0.22,1.99); I2 = 76%; p=0.01] stroke patients compared with control interventions, and using FES [SMD = 1.11; 95% CI (0.67,1.54); I2 = 11%; p < 0.00001]or visual feedback [SMD = 0.66; 95% CI (0.2,1.12); I2 = 4%; p = 0.005; ] as the feedback devices in BMI training was more effective than using robot. In addition, BMI-based training was more effective in improving patients' ADL than control interventions. There was no statistical difference in the dropout rate and adverse effects between the BMI-based training group and the control group. Conclusion: BMI-based training improved upper limb motor function and ADL in post-stroke patients. BMI combined with FES or visual feedback may be a better combination for functional recovery than robot. BMI-based trainings are well-tolerated and associated with mild adverse effects.